Omics disciplines and tuberculosis in Peru: impact, diagnosis and treatment - Guio, Heinner (2022)
After the publication of the human genome data, different lines of research have been generated in the fields of biology, biotechnology, drug development and even historical implications to understand the mechanisms of evolution and migration of human beings on the planet.